2016
DOI: 10.1152/ajpheart.00595.2015
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal neonatal myocardial adaptation is associated with loss of tolerance to tachycardia: a simultaneous invasive and noninvasive assessment

Abstract: Fortin-Pellerin E, Khoo NS, Mills L, Coe JY, Serrano-Lomelin J, Cheung PY, Hornberger LK. Postnatal neonatal myocardial adaptation is associated with loss of tolerance to tachycardia: a simultaneous invasive and noninvasive assessment. Am J Physiol Heart Circ Physiol 310: H598 -H607, 2016. First published December 30, 2015; doi:10.1152/ajpheart.00595.2015-Doppler studies at rest suggest left ventricular (LV) diastolic function rapidly improves from the neonate to infant. Whether this translates to its response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…In both views, there is possibility to determine the diameter of the aortic valve. This can be used for calculation of cardiac output as shown by Fugelseth et al, Fortin-Pellerin et al, and Solevåg et al (6, 19, 29). Tilting toward the right side of the thorax allowed the RVOT, the pulmonary valve (PV) and the main pulmonary artery (MPA) to be visualized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In both views, there is possibility to determine the diameter of the aortic valve. This can be used for calculation of cardiac output as shown by Fugelseth et al, Fortin-Pellerin et al, and Solevåg et al (6, 19, 29). Tilting toward the right side of the thorax allowed the RVOT, the pulmonary valve (PV) and the main pulmonary artery (MPA) to be visualized.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of apnea was not necessary to achieve adequate image quality. Other TTE planes like four-chamber view, or subcostal and apical five-chamber planes can be visualized as well, but may need more experience, as shown by Solevåg et al in piglets weighing ~2 kg (29) and shown by Fortin-Pellerin et al (19) or Fugelseth et al (26). Other studies have shown that TTE can also be done in the right lateral, supine position as well as in the left lateral, half supine position (6, 26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were completed in 2016. Partial data from two of the groups (NP, YP) has been previously published (6). With the exception of Table 1, which shows that the groups were comparable at baseline, no direct statistical comparisons were made between subjects from the 3 series of experiments (see statistical analysis section for details).…”
Section: Methodsmentioning
confidence: 99%
“…Using a piglet model of rapid atrial pacing, we previously demonstrated that tolerance to tachycardia actually decreases in the first few weeks ( 6 ), a finding associated with differences in the twist pattern of the left ventricle (LV). Whether changes in preload and afterload impact the tolerance of the neonatal and young infant heart to tachycardia is not certain.…”
Section: Introductionmentioning
confidence: 99%